PENERAPAN MULTIMEDIA AUDIO VISUAL PADA KEJUARAAN NASIONAL VIRTUAL PENCAK SILAT SENI THS-THM INDONESIA - Suni, Eugenius Kau (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. During the Covid-19 pandemic, almost all activities, including the development of Indonesian martial art culture, Pencak Silat, were conducted virtually. The National Coordinator of the Tunggal Hati Seminari-Tunggal Hati Maria Pencak Silat Organization (THS-THM) was supported by lecturers from Atma Jaya Catholic University of Indonesia, Jakarta, as well as IT practitioners from Amreci Teknologi Indonesia, to organize the National Pencak Silat Championship (Kejurnas) virtually using multimedia audiovisual implementation throughout its events. One of the challenges faced during the implementation of multimedia audiovisual was the uneven knowledge of the martial artists regarding multimedia, such as content creation, filming and editing techniques, the use of IT applications and teleconferencing, as well as issues with stable internet services for virtual communication in all regions. Therefore, the implementation of multimedia audiovisual in the Pencak Silat Championship required initial knowledge transfer through training in multimedia content creation, IT training, and the development of virtual communication guidelines, held online from January 2nd, 2021, to March 1st, 2021. With this training and guideline creation, the Kejurnas successfully provided an opportunity for the martial artists to achieve national recognition and improved the competence of the participants in multimedia content creation and mastery of telecommunications and information technology. Abstrak. Di masa pandemi Covid-19 hampir semua bidang kegiatan digelar secara virtual, termasuk kegiatan pengembangan budaya pencak silat Indonesia seperti Kejuaraan Nasional (Kejurnas) Pencak Silat. Koordinatorat Nasional (Koornas) Organisasi Pencak Silat Pendidikan Tunggal Hati Seminari-Tunggal Hati Maria (THS-THM) didukung oleh para dosen dari Universitas Katolik Indonesia Atma Jaya Jakarta serta praktisi IT Amreci Teknologi Indonesia menggelar Kejurnas pencak silat seni secara virtual dengan menerapkan implementasi multimedia audio visual pada seluruh rangkaian kegiatannya. Permasalahan yang dihadapi dalam penerapan multimedia audio visual adalah tidak meratanya pengetahuan para pesilat terkait multimedia, seperti pembuatan konten, teknik pengambilan gambar dan editing, penggunaan aplikasi IT dan teleconference serta masalah layanan internet untuk komunikasi virtual tidak selalu stabil di semua daerah. Sehingga pelaksanaan penerapan multimedia audio visual pada Kejurnas Pencak Silat ini perlu dimulai dengan transfer pengetahuan terlebih dahulu melalui pelatihan pembuatan konten multimedia, pelatihan bidang IT, dan penyusunan panduan komunikasi virtual pada tanggal 02 Januari 2021 hingga 01 Maret 2021 secara daring. Dengan pelatihan dan pembuatan panduan ini, pelaksanaan Kejurnas berhasil memberikan kesempatan kepada para pesilat untuk tetap mengukir prestasi di tingkat nasional, juga meningkatkan kompetensi para pesilat dalam hal pembuatan konten multimedia dan penguasaan teknologi telekomunikasi dan informatika.